1994
DOI: 10.1152/jn.1994.72.2.785
|View full text |Cite
|
Sign up to set email alerts
|

Effect of muscimol microinjections into the prepositus hypoglossi and the medial vestibular nuclei on cat eye movements

Abstract: 1. For horizontal eye movements, previous observations led to the hypothesis that the legendary neural integrator necessary for correct gaze holding, adequate vestibuloocular reflex (VOR), and optokinetic nystagmus, was located in the region of the complex formed by the nucleus prepositus hypoglossi (NPH) and the medial vestibular nucleus (MVN). 2. The aim of the present study was to test the respective contributions of the NPH, of the rostral part of the MVN, which contains most second-order vestibular neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
59
0
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 27 publications
3
59
0
2
Order By: Relevance
“…However, the eyes drifted back toward the primary position with a longer time constant (about 1P4 s) than after a NPH lesion (Robinson, 1974;Godaux & Vanderkelen, 1984). In addition to a gaze-holding failure, lesions of the NPH (Cheron et al 1986 b), and its inactivation by muscimol microinjections (Mettens et al 1994), also induced VOR abnormalities consistent with a loss of the eye-position signal. This favours the hypothesis of a common neural integrator, since a brain lesion inducing abnormality of one ocular subsystem while sparing another subsystem would have ruled out the existence of such a common integrator.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…However, the eyes drifted back toward the primary position with a longer time constant (about 1P4 s) than after a NPH lesion (Robinson, 1974;Godaux & Vanderkelen, 1984). In addition to a gaze-holding failure, lesions of the NPH (Cheron et al 1986 b), and its inactivation by muscimol microinjections (Mettens et al 1994), also induced VOR abnormalities consistent with a loss of the eye-position signal. This favours the hypothesis of a common neural integrator, since a brain lesion inducing abnormality of one ocular subsystem while sparing another subsystem would have ruled out the existence of such a common integrator.…”
mentioning
confidence: 94%
“…That first hypothesis of Robinson, concerning the existence of an oculomotor integrator, has been proved experimentally. The major part of the oculomotor neural integrator(s) has (have) been located in the nucleus prepositus hypoglossi (NPH) for horizontal movements (Cheron, Godaux, Laune & Vanderkelen, 1986 b;Cannon & Robinson, 1987;Cheron, Mettens & Godaux, 1992;Mettens, Godaux, Cheron & Galiana, 1994) and in the interstitial nucleus of Cajal for vertical movements (Fukushima, 1987;Crawford, Cadera & Vilis, 1991) and for torsional movements (Crawford et al 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It uses eye-velocity-coded saccadic commands and head-velocity vestibular signals to generate eye-position commands (Fukushima and Kaneko 1995;Moschovakis 1997). For the horizontal plane, the prepositus hypoglossi nucleus (PHN) is the principal structure of the oculomotor integrator (Mettens et al 1994) as shown by comparison among network modeling and pharmacological for lesion experiments (Arnold et al 1999;Cannon and Robinson 1987;Chéron and Godaux 1987;Robinson 1975;Skavenski and Robinson 1973). The PHN is in the rostral medulla (McCrea and Horn 2005), near the medial vestibular nucleus (MVN), which is one of its major inputs.…”
Section: Introductionmentioning
confidence: 99%
“…For this procedure, the only difference between analyzing VOR and fixation data is the presence or absence of a non-zero head-velocity term in the oculomotor integrator equation. In the DISCUSSION, we compare this method to other methods (Mettens et al 1994;Rey and Galiana 1993;Schneider et al 2000) developed to fit eye data from an animal with an imperfector integrator performing saccades.…”
Section: Introductionmentioning
confidence: 99%